Amadou Fane - Bouwèrè, Mali - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Amadou Fane is both a farmer and a blacksmith from the village of Bouwéré in Mali. He describes how he built a seeder to use micro-dosing technique on his farm and how this has helped to optimize the use of fertilizers as well as increase his yields. The seeder and the new techniques in farming were needed since the climate has changed along with less fertile soil, space and yields. The villagers have now adapted to the changes by including new ways of farming.